Optimizing Douglas-fir bark liquefaction in mixtures of glycerol and polyethylene glycol and KOH - Esteves, Bruno (2018)
The outer bark of Douglas-fir (Pseudotsuga menziesii) has a significant amount of cork tissue that may be an important source of chemicals derived from its natural polymers, suberin, cellulose, hemicelluloses and lignin. The present work focuses on the polyalcohol liquefaction of Douglas-fir bark with glycerol and polyethylene glycol (PEG) in order to obtain a liquid that can be further processed to other chemicals and products. The results show that Pseudotsuga bark can be liquefied in a significant percentage in presence of alkali. The best liquefaction yield was obtained with 6% KOH as agents. Although the use of a cosolvent is favorable, good liquefaction yields can also be obtained by glycerol alone. Lower temperatures are favorable as they lead to acceptable liquefaction yields. FTIR-ATR studies showed that all the structural compounds of the bark were attacked and depolymerized. The process tested has a high potential for generation of value-added products from liquefied Douglas-fir bark.